Methods of Fertilizer Application in Pinus patula - Singh, S. B.; Prasad, K. G.; Hillary, S. F.; Maurya, G. S. (Indian Forester, 1985)
Randomized block design field experiment to evaluate different methods of fertilizer application in two year old Pinus patula plantation was conducted at Paymund. Ooty. The treatment consisted of control (To) and fertilizer application (100 g urea+100 g superphosphate+25 g muriate of potash) by broadcast (T1) intrench to full circumference equivalent to canopy diameter (T2), and in trench to full circumference equivalent to canopy diameter (T3) replicated 3 times. Intially broadcast application increased height growth. After 3 months, trench application to full circumference (T3), was superior over other methods of fertilizer application.